Factors Influence The Usage of Data Analytics in Audit Procedure By Internal Auditor of Central Bank in Malaysia - Hannan Zamilah, Hamdi (2023)
The emerging use of technology give an impact to audit profession in a way that more IT auditors are needed in the organization to conduct audit procedure with the help of technology or Computer Assisted Audit Techniques (CAATs) like data analytics as it deemed to be as helpful tool in expediting the work of auditors. Therefore, current study analyzed the correlation between performance expectancy, effort expectancy, social influence, facilitating conditions and IT skills on intention to use data analytics, as well as analyzing the correlation between facilitating conditions, IT skills and intention to use on actual usage of data analytics. The variables used in this study was adopted from Unified Theory of Acceptance and Use of Technology (UTAUT) and IT Competency theory. Data was collected in the form of online survey from 72 internal auditors in the internal audit department of central bank in Malaysia, and the analysis of data was conducted using SmartPLS. The findings of the study suggest that performance expectancy, social influence and facilitating conditions have a positive significant influence on internal auditor’s intention to use data analytics, however effort expectancy has no significant influence on intention to use. Meanwhile, IT skills and intention to use have positive significant influence on the actual usage of data analytics by central bank’s internal auditors. This study contributed to both theoretical and practical implications where UTAUT and IT competency theory are proven, and reader can gain insights on the perception of central bank’s internal auditors on data analytics in conducting audit procedure. Future research can expand the study by collecting data from other financial institutions in Malaysia.